Effects of mixed application of effective microorganisms (EM) and soil amendments on agronomic characteristic and quality of flue-cured tobacco - Wei Kesu; Hu Tingting; Li Delun; Tu Yonggao; Yu Liangji; Tu Guangjun (浙江大学学报. 农业与生命科学版, 2015)
Flue-cured tobacco is a major cash crop in China. Due to the scarcity of land resources, continuous cropping of tobacco was very common all over the country. However, the continuous cropping phenomenon would lead to change of soil properties and nutrient imbalance, seriously affecting yield and economic merits of tobacco. Therefore, it was quite necessary to optimize the soil microbial environment and promote the effective absorption and utilization of fertilizers, to improve the yield and quality of flue-cured tobacco. It has been reported that soil amendments could improve the physical and chemical properties of soil, as well as the nutrient status, which could also regulate pH and organic matter of soil to increase the availability of N, P and K contents. In a word, soil amendments were effective to promote the productivity of degraded soils. Microbial fertilizer could improve the micro-environment of plant rhizosphere, by increasing the diversity of microbial species and improving growth and nutrient absorption capacity of root.There have been many reports about the effect of microbial fertilizer or soil amendment application on growth and development of crops, but the mixed application effect of microbial fertilizer and soil amendments was rarely mentioned. In this study, the combining effects of effective microorganisms (EM) and soil amendments on agronomic characteristic and quality of flue-cured tobacco were investigated.A field trial designed as randomized block was carried out to reveal the effects of EM and soil amendment treatments (T1: conventional film transplanting; T2: conventional film transplanting + EM + soil amendments; T3: well cellar type transplanting; T4: well cellar type transplanting + EM + soil amendments) on leaves, root and stem development of flue-cured tobacco during the growth period. Meanwhile, the effects of different treatments on yield and quality of flue-cured tobacco were discussed.The results showed that the mixed application of EM and soil amendments promoted the growth of tobacco plant, especially at the maturity stage. Simultaneously, the mixed application of EM and soil amendments also improved the yield and quality of tobacco leaves, and optimized the grade of tobacco leaves. The yields of T2 and T4 treatments were 1 909.31 kg/hm2 and 2 134.91 kg/hm2, which were higher than those of T1 and T3 by 5.21% and 7.13%, respectively. The output values of T2 and T4 were 29 460.69 Chinese Yuan/hm2 and 35 162.05 Chinese Yuan/hm2, higher than those of corresponding controls (T1 and T3) by 3.84% and 8.72%, respectively. For chemical composition, the mixed application of EM and soil amendments increased the contents of nicotine, potassium and chlorine, but decreased the content of total sugar in flue-cured tobacco leaves. Furthermore, the mixed application of EM and soil amendments reduced the Schmuck value and the ratio of total sugar to nicotine, increased the ratio of reducing sugar to total sugar. The treatments with EM and soil amendments enhanced the sensory quality of flue-cured tobacco leaves, and the total scores of T2 and T4 increased 2.30 and 2.67, respectively, compared with the corresponding controls (T1 and T3) .In a word, the mixed application of EM and soil amendments shows practical value not only in improving the grade of the flue-cured tobacco leaves, but also improving their yields and quality.